2021
DOI: 10.22271/j.ento.2021.v9.i2a.8452
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and insecticidal properties of some botanical extracts against the lesser grain borer, Rhyzopertha dominica F. (Coleoptera: Bostrichidae)

Abstract: UMYUK) Nigeria, to analyze phytochemical properties and assess insecticidal effects of acetonic leaf extracts of Euphorbia balsamifera, Lawsonia inermis and Mitracarpus hirtus against Rhyzopertha dominica F. To analyze the phytochemicals of the test plants, preliminary tests were conducted to determine secondary metabolites while Gas Chromatography Mass Spectrum (GC-MS) was carried out to identify various active compounds present in the botanical extracts. Effects of the treatments on adult mortalities against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This finding concurs with a previous report that ethanolic leaf extract of M. hirtus caused total mortality of S. zeamais at 3 DAT when applied at 50.00 mgml -1 [34] . Another report indicated that 100.00 mgml -1 acetone extract of M. hirtus resulted in 63.33% adult mortality of R. dominica at 7 DAT [24] . This study has revealed that high mortality of insects exposed to plant extracts might have exhibited contact toxicity against the weevils as suggested by Hikal et al [35] .…”
Section: Discussion 41 Effect Of Chloroform Leaf Extracts Of Selected Botanicals On Adult Mortality Of S Zeamaismentioning
confidence: 99%
See 3 more Smart Citations
“…This finding concurs with a previous report that ethanolic leaf extract of M. hirtus caused total mortality of S. zeamais at 3 DAT when applied at 50.00 mgml -1 [34] . Another report indicated that 100.00 mgml -1 acetone extract of M. hirtus resulted in 63.33% adult mortality of R. dominica at 7 DAT [24] . This study has revealed that high mortality of insects exposed to plant extracts might have exhibited contact toxicity against the weevils as suggested by Hikal et al [35] .…”
Section: Discussion 41 Effect Of Chloroform Leaf Extracts Of Selected Botanicals On Adult Mortality Of S Zeamaismentioning
confidence: 99%
“…This was possible because plant species contain secondary metabolites which are vast storehouse of compounds such as the steroids, phenolic compounds and tannins with wide range of biological activity reported to have great impact on insecticidal activities [35,37] . Other bioactive compounds such as terpenoids, flavonoids, alkaloids, saponins and glycosides were found in the leaf extracts of E. balsamifera, L. inermis and M. hirtus [24] . GC-MS analysis confirmed the presence of different compounds sucn as oileic acid Eicosyl ester, decanoic acid, hydrogen peroxides and N,N-diethyl nediamine in acetonic leaf extracts of E. balsamifera, L. inermis and M. hirtus and found to have some insecticidal properties [24] .…”
Section: Discussion 41 Effect Of Chloroform Leaf Extracts Of Selected Botanicals On Adult Mortality Of S Zeamaismentioning
confidence: 99%
See 2 more Smart Citations
“…One of the challenges of the application of plant products as bio-pesticides in Nigeria is that most of the data are obtained from laboratory experiments with little from field trials. Abubakar et al [93] observed that most of the laboratory evaluations did not address the aspect of lethal concentrations of botanicals against insect pests. It is important that researchers need to look into this aspect to investigate on lethal doses/concentrations of various botanicals with insecticidal potentials.…”
Section: Challenges and Their Strategic Solutions To Utilization Of B...mentioning
confidence: 99%